PENINGKATAN KESADARAN MASYARAKAT TENTANG HIPERTENSI DI DESA BOBO - Sumarto, Sabaria; Ujabid, Sukmawati; Teapon, Ferista; Lestari, Tutik (MAJU : Indonesian Journal of Community Empowerment, 2025)
Hypertension is a chronic condition characterized by elevated blood pressure, often called a "silent killer" due to its asymptomatic nature and severe complications. This community service activity aimed to increase knowledge about hypertension among women and elderly in Desa Bobo RT 01, addressing the growing public health concern of hypertension prevalence in Indonesia. The method involved direct educational sessions using posters, PowerPoint presentations, and pre- and post-tests to evaluate participants' understanding. Fifteen respondents participated, showing a significant improvement in hypertension knowledge after the intervention. The average knowledge score increased from 8.67 to 9.53, indicating the effectiveness of the health education in raising awareness about risk factors, prevention, and management of hypertension. This activity highlights the importance of community-based education to promote healthy lifestyles and prevent hypertension-related complications.